Diagnostic Error in Correctional Mental Health: Prevalence, Causes, and Consequences. (April 2016) - Martin, Michael S.; Hynes, Katie; Hatcher, Simon; Colman, Ian
While they have important implications for inmates and resourcing of correctional institutions, diagnostic errors are rarely discussed in correctional mental health research. This review seeks to estimate the prevalence of diagnostic errors in prisons and jails and explores potential causes and consequences. Diagnostic errors are defined as discrepancies in an inmate's diagnostic status depending on who is responsible for conducting the assessment and/or the methods used. It is estimated that at least 10% to 15% of all inmates may be incorrectly classified in terms of the presence or absence of a mental illness. Inmate characteristics, relationships with staff, and cognitive errors stemming from the use of heuristics when faced with time constraints are discussed as possible sources of error. A policy example of screening for mental illness at intake to prison is used to illustrate when the risk of diagnostic error might be increased and to explore strategies to mitigate this risk.